Characteristic roadmap of linker governs the rational design of PROTACs - Yawen Dong; Tingting Ma; Ting Xu; Zhangyan Feng; Yonggui Li; Lingling Song; Xiaojun Yao; Charles R. Ashby, Jr; Ge-Fei Hao (Elsevier, 2024)
Proteolysis targeting chimera (PROTAC) technology represents a groundbreaking development in drug discovery, leveraging the ubiquitin‒proteasome system to specifically degrade proteins responsible for the disease. PROTAC is characterized by its unique heterobifunctional structure, which comprises two functional domains connected by a linker. The linker plays a pivotal role in determining PROTAC's biodegradative efficacy. Advanced and rationally designed functional linkers for PROTAC are under development. Nonetheless, the correlation between linker characteristics and PROTAC efficacy remains under-investigated. Consequently, this study will present a multidisciplinary analysis of PROTAC linkers and their impact on efficacy, thereby guiding the rational design of linkers. We will primarily discuss the structural types and characteristics of PROTAC linkers, and the optimization strategies used for their rational design. Furthermore, we will discuss how factors like linker length, group type, flexibility, and linkage site affect the biodegradation efficiency of PROTACs. We believe that this work will contribute towards the advancement of rational linker design in the PROTAC research area.